2015
DOI: 10.1111/adb.12235
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-dependent inhibition of glutamatergic transmission on nucleus accumbens medium spiny neurons by the abused inhalant toluene

Abstract: Abused inhalants are voluntary inhaled at high concentrations to produce intoxicating effects.Results from animal studies show that the abused inhalant toluene triggers behaviors, such as selfadministration and conditioned place preference that are commonly associated with addictive drugs. Little is known however about how toluene affects neurons within the nucleus accumbens (NAc), a brain region within the basal ganglia that mediates goal-directed behaviors and is implicated in the development and maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
3
10
0
2
Order By: Relevance
“…Using D2-Cre reporter rats, this effect was found to be restricted to NAc shell D2+ MSNs and was accompanied by changes in electrophysiological parameters recorded from these neurons. These findings are consistent with and add to findings from previous studies reporting selective effects of toluene on neurons within the addiction neurocircuitry that vary based on brain region, neuronal cell-type and projection target (Beckley et al, 2016;Wayman and Woodward, 2018b). The mechanism underlying the selective effect of toluene on D2+ MSN intrinsic excitability observed in this study is currently unknown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using D2-Cre reporter rats, this effect was found to be restricted to NAc shell D2+ MSNs and was accompanied by changes in electrophysiological parameters recorded from these neurons. These findings are consistent with and add to findings from previous studies reporting selective effects of toluene on neurons within the addiction neurocircuitry that vary based on brain region, neuronal cell-type and projection target (Beckley et al, 2016;Wayman and Woodward, 2018b). The mechanism underlying the selective effect of toluene on D2+ MSN intrinsic excitability observed in this study is currently unknown.…”
Section: Discussionsupporting
confidence: 92%
“…et al 10.3389/fnins.2023.1235866 Frontiers in Neuroscience 07 frontiersin.org synaptic signaling was observed in glutamatergic pyramidal neurons in the mPFC and basolateral amygdala following bath application of toluene (Beckley and Woodward, 2011;Woodward, 2023). D2 MSNs in the NAc have been shown to undergo eCB-mediated LTD (Grueter et al, 2010) as well as depolarization-induced suppression of excitation (DSE) that also involves endocannabinoid signaling (Kreitzer and Regehr, 2001;Beckley et al, 2016). Whether in vivo exposure to toluene vapor induces LTD or DSE in NAc D2 MSNs is not known but these events could trigger compensatory changes that underlie the increase in intrinsic excitability of D2 NAc shell MSNs observed during injections of low to moderate amounts of current.…”
Section: Discussionmentioning
confidence: 99%
“…This could reflect changes in neural signaling induced by repeated toluene exposures that outlast the brief period of active vapor inhalation. Although not tested in the present study, we have previously shown that acute exposure of brain slices to toluene induces a long-lasting, endocannabinoid-dependent reduction in AMPA-mediated synaptic glutamatergic signaling in the medial prefrontal cortex ( Beckley and Woodward, 2011 ) and nucleus accumbens ( Beckley et al, 2016 ). Future studies could investigate whether manipulating endocannabinoid signaling alters the pattern of toluene self-administration.…”
Section: Discussionmentioning
confidence: 91%
“…Los inhalables de tipo solventes de pegamento tienen una rápida absorción por parte del organismo, y actúan en los órganos más ricos en lípidos, como es la estructura cerebral (Müller & Kornhuber, 2017;Tormoehlen et al, 2014). Así que una exposición crónica de altos niveles de pureza de la sustancia durante largos periodos de tiempo y un volumen demasiado elevado de pegamento en el torrente sanguíneo pueden originar desmotivación, una persistencia mnésica de experiencias desagradables y alteraciones cognitivas, que son el resultado de cambios dopaminérgicos en el sistema mesolímbico y núcleo accumbens; algo muy similar a lo que sucede en la abstinencia (Beckley et al, 2015;Cruz, 2011;Howard et al, 2010;Tormoehlen et al, 2014;Wayman & Woodward, 2018).…”
Section: Núcleo Accumbensunclassified
“…Una diversidad de trabajos de investigación realizados a partir del modelo animal refieren que el abuso de inhalables puede provocar alteraciones en la vía de distribución dopaminérgica y regiones asociadas, como es el caso del área tegmental ventral y del núcleo accumbens (Beckley et al, 2015;Bowen, Batis, Paez-Martínez, & Cruz, 2006;Cruz, 2011;Howard et al, 2010;Tormoehlen, Tekulve, & Nañagas, 2014;Wayman & Woodward, 2018). Inclusive, las proyecciones que se producen desde la misma región tegmental ventral hacia el núcleo accumbens a través de la vía de recompensa cerebral meso-accumbens parten del sistema mesolímbico (Figura 1) y se han considerado como las responsables de la conducta adictiva (Bowen et al, 2006;Cairney, Maruff, Burns, & Currie, 2002;Da Silva, 2018).…”
Section: Introduccionunclassified